Let the games begin - Mazarura, Rufaro Faith (Flatiron Books, 2024)
"Set against a sizzling-hot Greek summer filled with sunshine and souvlaki, Rufaro Faith Mazarura's Let the Games Begin is a page-turning debut rom-com about two strangers at the top of their game. Athens, 2024. Olivia Nkomo has always been ambitious, smart, and an overall go-getter. Now that she's graduated from university, she's willing to do whatever it takes to land her dream job at the Summer Games. The first step? Securing her new internship, which will put her in the center of all the action, where she hopes to run into some of her favorite athletes. Ezekiel "Zeke" Moyo, the heartthrob star runner of Team Great Britain, is more than ready to claim his title as the fastest man in the world, following in the footsteps of the greatest athletes of all time. His future to the finish line is looking bright--despite his recent breakup with celebrated gymnast Valentina Ross-Rodriguez constantly making headlines. When Olivia and Zeke collide--literally--on the first day of training, sparks fly. As the games grow closer, so do Olivia and Zeke. But the competition starts stirring up uncomfortable memories from Zeke's past . . . and Olivia's internship doesn't turn out to be what she expected. Will they be able to overcome these hurdles and achieve their dreams? Or will it come at the cost of their budding romance?"--